Antibody-based and cell therapies for advanced mastocytosis: established and novel concepts - Valent, Peter; Akin, Cem; Arock, Michel; Gleixner, Karoline V.; Greinix, Hildegard; Hermine, Olivier; Horny, Hans-Peter; Ivanov, Daniel; Orfao, Alberto; Rabitsch, Werner; Reiter, Andreas; Schulenburg, Axel; et al. (International journal of molecular sciences, 2023)
Advanced systemic mastocytosis (SM) is a heterogeneous group of myeloid neoplasms characterized by an uncontrolled expansion of mast cells (MC) in one or more internal organs, SM-induced tissue damage, and poor prognosis. Advanced SM can be categorized into aggressive SM (ASM), MC leukemia (MCL), and SM with an associated hematologic neoplasm (SM-AHN). In a vast majority of all patients, neoplastic cells display a KIT mutation, mostly D816V and rarely other KIT variants. Additional mutations in other target genes, such as SRSF2, ASXL1, or RUNX1, may also be identified, especially when an AHN is present. During the past 10 years, improved treatment approaches have led to a better quality of life and survival in patients with advanced SM. However, despite the availability of novel potent inhibitors of KIT D816V, not all patients enter remission and others relapse, often with a multi-mutated and sometimes KIT D816V-negative disease exhibiting multi-drug resistance. For these patients, (poly)chemotherapy, antibody-based therapies, and allogeneic hematopoietic stem cell transplantation may be viable treatment alternatives. In this article, we discuss treatment options for patients with drug-resistant advanced SM, including novel KIT-targeting drugs, antibody-based drugs, and stem cell-eradicating therapies.
Gesehen am 19.03.2024